PERMODELAN BATUAN ANISOTROP DENGAN MENGGUNAKAN METODE ELEMEN HINGGA - Arbiansyah (NIM 22198027), Muhammad
Abstract : Underground excavation modelling in geomechanics is usually take with general assumption like isotrophy, continu and homogen. The fact is that rock mass in the nature have characteristic like anisotrophy, not homogen and have discontinuities. The next developing in modelling activity in underground excavation should take with the nature characteristic for the rock mass. Research in rock anisotrophy modelling will take with finite element method (PHASE2 Modeler) and the assumption for the material is transversely isotropic. The result in this research are : 1. Anisotrophy characteristic is not significantly influence the result of the Ma ess distribution around the hole of underground excavation 2. Anisotrophy characteristic is significantly influence the result of the displacement around the hole of underground excavation In this research, the result of underground excavation modelling will have the same condition with the underground excavation modelling in the nature with the increasing of the dimension of the model. This fact explained that the stress distribution far from around the hole excavation will move to the original stress and the displacement far from around the hole excavation will move too little displacement or there are no displacement. The research in rock anisotrophy modelling should be continued with another anisotrophy material, so the research will increasing the understanding of rock anisotrophy behaviour in the underground excavation modelling.